Co-locating offshore renewable energy farms with low-trophic aquaculture: recent developments and future challenges - Hanxiao Ma; M Salauddin (Environmental Research: Energy)
The escalating threat of global warming, exacerbated by increasing human activities, presents significant challenges for coastal environments and has led to conflicts between the use of marine space and the conservation of marine resources. A sustainable co-location approach to marine management, aims to restore marine ecosystems, mitigate climate change, and reduce marine spatial conflicts by placing offshore renewable energy (ORE) farms alongside low-trophic aquaculture (LTA). This systematic literature review analyses the strengths and limitations of the co-location method, and the findings suggest a strong potential for its development in offshore areas. The ORE farms and LTA farms can share space, vessels, and wave attenuation effects with each other. The renewable energy farms can supply power and provide anchors for the aquaculture system, while the low-trophic species capture carbon and nutrients in their ambient water. However, this multi-use strategy is still in its early stages and presents significant knowledge gaps that must be addressed before it can be widely implemented on a global scale. Previous field investigations and academic studies have been largely one-dimensional and insufficient. Critical issues in environmental, technical, and socio-economic domains remain unaddressed, underscoring the urgent need for comprehensive solutions.